2022
DOI: 10.1111/gcb.16300
|View full text |Cite
|
Sign up to set email alerts
|

Encroachment diminishes herbaceous plant diversity in grassy ecosystems worldwide

Abstract: Woody encroachment is ubiquitous in grassy ecosystems worldwide, but its global impacts on the diversity of herbaceous plants that characterise and define these ecosystems remain unquantified. The pervasiveness of encroachment is relatively easily observed via remote sensing, but its impacts on plant diversity and richness below the canopy can only be observed via field‐based studies. Via a meta‐analysis of 42 field studies across tropical to temperate grassy ecosystems, we quantified how encroachment altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 126 publications
1
19
1
Order By: Relevance
“…This question is especially relevant in semi‐arid grasslands, which are increasingly experiencing shrub encroachment (Bai et al, 2020; Maestre et al, 2009). Shrub encroachment, that is, increases in the density, coverage and biomass of shrubs, is an important ecological and environmental problem faced by global grassland ecosystems (Eldridge et al, 2011; Ratajczak et al, 2012; Wieczorkowski & Lehmann, 2022). Studies have shown that nearly 10%–20% of the area in semi‐arid regions are experiencing shrub encroachment (Reynolds et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This question is especially relevant in semi‐arid grasslands, which are increasingly experiencing shrub encroachment (Bai et al, 2020; Maestre et al, 2009). Shrub encroachment, that is, increases in the density, coverage and biomass of shrubs, is an important ecological and environmental problem faced by global grassland ecosystems (Eldridge et al, 2011; Ratajczak et al, 2012; Wieczorkowski & Lehmann, 2022). Studies have shown that nearly 10%–20% of the area in semi‐arid regions are experiencing shrub encroachment (Reynolds et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of open savanna, the main natural driver, likely supports higher megafauna biomass by promoting savanna heterogeneity (e.g., grassland-woodland mosaics) and, as a result, increasing megafauna functional diversity 55,56 . This result also reiterates the threat posed by bush encroachment on Africa's biodiversity and ecological functioning 57,58 , and why management actions that may favour woody encroachment for other purposes (e.g. carbon sequestration) are ill advised 59 .…”
Section: The Relative Roles Of Natural and Anthropogenic Drivers In Pasmentioning
confidence: 56%
“…The composition dissimilarities between burned plots suggest that the fire legacy shapes different plant communities. Eight years of fire exclusion led to the beginning of woody encroachment, with the presence of tree species (absent in burned plots), which may lead to a loss of resilience in these plant communities, resulting in a decrease in species and functional diversity as well as changes in the state and functioning of the community (Hoffmann et al, 2012; Abreu et al, 2017; Wieczorkowski & Lehmann, 2022). Therefore, the presence of fire and how often the area is burned will influence both the maintenance of Cerrado open savannas and their diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Woody species may encroach into savannas rapidly in the absence of fire: in a 4‐year period, a great increase in species richness and the density of trees and generalist species could be observed in FE savannas (Pilon, 2019). This process of encroachment can have several consequences for the system, such as alterations in the structure and diversity, thus affecting its functional composition and functioning (Abreu et al, 2017; Pilon, Cava et al, 2021; Wieczorkowski & Lehmann, 2022). Moreover, woody encroachment would alter the local fire behavior due to changes in the fuel load quantity and type, and as a consequence, the flammability of the system (Newberry et al, 2020).…”
Section: Discussionmentioning
confidence: 99%